Management of social media as a Branding Tool by the Madrasah Aliyah Editorial Team - Khalilah Ramadhani; Erna Setyowati (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This research aims to examine social media management as a way of branding at Madrasah Aliyah Negeri (MAN) Batu City by a special team called the Editorial Team, which is made up of public relations professionals. This study took a qualitative approach and conducted case study research. Data was gathered using interviews, observation, documentation techniques, and data analysis techniques applied in three steps: data condensation, data presentation, and conclusion. The data obtained is checked for the validity of the data using the triangulation technique. The findings show that MAN Batu City's branding is professionally carried out by the Editorial Team using social media, with due regard for the selection of publication techniques, targeting, and situation determination, as well as the time of publication during branding implementation. Branding is carried out ideally through the Editorial Team's orderly coordination of information management in partnership with online media to support suitable facilities and operate following their respective tasks.